Chronic Kidney Disease and Pulse Wave Velocity: A Narrative Review - Toussaint, Nigel D.; Cameron, James D.; Hawley, Carmel M.; Lioufas, Nicole (International journal of hypertension, 2019)
Chronic kidney disease (CKD) is associated with excess cardiovascular mortality, resulting from both traditional and nontraditional, CKD-specific, cardiovascular risk factors. Nontraditional risk factors include the entity Chronic Kidney Disease–Mineral and Bone Disorder (CKD-MBD) which is characterised by disorders of bone and mineral metabolism, including biochemical abnormalities of hyperphosphatemia and hyperparathyroidism, renal osteodystrophy, and vascular calcification. Increased arterial stiffness in the CKD population can be attributed amongst other influences to progression of vascular calcification, with significant resultant contribution to the cardiovascular disease burden. Pulse wave velocity (PWV) measured over the carotid-femoral arterial segments is the noninvasive gold-standard technique for measurement of aortic stiffness and has been suggested as a surrogate cardiovascular end-point. A PWV value of 10 m/s or greater has been recommended as a suitable cut-off for an increased risk of cardiovascular mortality. CKD is a risk factor for an excessive rate of increase in aortic stiffness, reflected by increases in PWV, and increased aortic PWV in CKD shows faster progression than for individuals with normal kidney function. Patients with varying stages of CKD, as well as those on dialysis or with a kidney transplant, have different biological milieu which influence aortic stiffness and associated changes in PWV. This review discusses the pathophysiology of arterial stiffness with CKD and outlines the literature on PWV across the spectrum of CKD, highlighting that determination of arterial stiffness using aortic PWV can be a useful diagnostic and prognostic tool for assessing cardiovascular disease in the CKD population.